Cold tolerance of the invasive larch casebearer and implications for invasion success. (25th October 2018) - Ward, Samuel F.; Venette, Robert C.; Aukema, Brian H.
Abstract : Larch casebearer became established in North America in the late 1800s. Cold temperatures are considered a limiting factor for the insect's range, yet the cold hardiness of larch casebearer has never been quantified. We investigated (i) larval survival after acute and prolonged exposure to subzero temperatures and (ii) supercooling points (i.e. temperatures causing the onset of freezing) of overwintering and active larvae from November 2015 to April 2017. We developed models linking exposure temperatures to survival and evaluated them with larvae from field conditions. Historical minimum temperature data were used to estimate changes in survival across time at a site in northern Minnesota. The cold tolerance of larch casebearer changed significantly with season: both lower lethal temperatures and supercooling points were lowest in mid‐winter and highest in spring and autumn. For example, 50% survival was estimated after acute exposure to a mean ± SE temperature of −28.9 ± 1.77 °C in October, −40.8 ± 0.77 °C in January and −27.8 ± 1.00 °C in April. A model predicting survival using supercooling points provided conservative estimates of overwintering survival because it overestimated survival by approximately 4% and 8% in 2016 and 2017, respectively. Analysis of climate data suggested that overwintering survival could have increased significantly over the previous half century.